Creative Solution Focused Counseling Models (CSFCM): Strategi Kreatif untuk Mengembangkan Self-regulated Learning Siswa - Saputra, Wahyu Nanda Eka; Da Costa, Augusto; Alhadi, Said (Jurnal Kajian Bimbingan dan Konseling, 2024)
The study aimed to develop CSFCM to improve student self-regulated learning. CSFCM is an application of solution-focused counseling integrated with creative arts. The developmental research consisted of three stages: (1) identify the self-regulated learning level; (2) formulating a hypothetical draft of CSFCM to improve student self-regulated learning; and (3) conducting product feasibility testing by experts and practitioners. Data analysis technique used quantitative descriptive analysis. The results showed that the CSFCM which consisting five stages of counseling was categorized as feasible to be implement in the schools.